Development of Spherical Nucleic Acids for Prostate Cancer Immunotherapy - Qin, Lei; Wang, Shuya; Dominguez, Donye; Long, Alan; Chen, Siqi; Fan, Jie; Ahn, Jihae; Skakuj, Kacper; Huang, Ziyin; Lee, Andrew; Mirkin, Chad; Zhang, Bin (Frontiers in Immunology, 2020)
Although the strategy of therapeutic vaccination for the treatment of prostate cancer has advanced to and is available in the clinic (Sipuleucel-T), the efficacy of such therapy remains limited. Here, we develop Immunostimulatory Spherical Nucleic Acid (IS-SNA) nanostructures comprised of CpG adjuvant oligonucleotides and prostate cancer peptide antigens, and evaluate their antitumor efficacy in syngeneic mouse models of prostate cancer. IS-SNAs with the specific structure feature of presenting both antigen and adjuvant CpG on the surface (hybridized model (HM) SNAs) induce stronger cytotoxic T lymphocyte (CTL) mediated antigen-specific killing of target cells than that for IS-SNAs with CpG on the surface and antigen encapsulated within the core (encapsulated model (EM) SNAs). Mechanistically, HM SNAs increase the co-delivery of CpG and antigen to dendritic cells over that for EM SNAs or admixtures of linear CpG and peptide, thereby improving cross-priming of antitumor CD8+ T cells. As a result, vaccination with HM SNAs leads to more effective antitumor immune responses in two prostate cancer models. These data demonstrate the importance of the structural positioning of peptide antigens together with adjuvants within IS-SNAs to the efficacy of IS-SNAs-based cancer immunotherapy.